Residence time distribution studies using radiotracers in a lab-scale distillation column: Experiments and modeling. (December 2019) - El Korchi, K.; Alami, R.; Saadaoui, A.; Mimount, S.; Chaouch, A.
Abstract: The radiotracer's residence time distribution (RTD) is an important study of the performance of industrial process reactors.The application of radiotracers is the method used to diagnose the functioning of packed distillation columns. This paper presents the results of an experiment carried out using the Technitium-99 (Mo 99 ) radiotracer to determine the RTD in a laboratory-scale packed distillation column.The concentration of the radiotracer is monitored using eight scintillation detectors.The obtained data is treated for background correction, radioactive decay correction, starting point correction, filtering, and data extrapolation. After this preprocessing, two mathematical models are investigated on this data using International Atomic Energy Agency (IAEA) RTD software. The parameters of each model are optimized in oder to calculate the value of the RTD, and to determine the model which gives the best match with the experimental data. The appropriate model is than selected. Consequenly the one with the best match, is used to deduce the crucial parameter RTD in this experiment. Highlights: Determination the RTD in a laboratory-scale packed distillation column. Using Technetium-99 m radiotracers technique. Determination the theoretical model which gives the best match for experimental data.